IMPACT OF IRRIGATION INTERVALS AND ASCORBIC ACID CONCENTRATIONS ON SOME GROWTH AND ANATOMICAL CHARACTERISTICS OF THE SOYBEAN CROP - I. M. Ali; A. H. AbdulKafoor; Y. A. Al-Janabi; A. S. A. Ramadan (مجلة الأنبار للعلوم الزراعية, 2025)
The study was conducted at the College of Agriculture's research station in the Al-Bu'itha area. It aimed to determine how drought stress affects the growth and anatomical features of the soybean crop and how ascorbic acid lessens the negative effects of low water availability. The research applied a split-plot arrangement with three replications using a randomized complete block design (RCBD). It involved irrigating the main plots at intervals of 3, 6, 9, and 12 days, and applying ascorbic acid spray concentrations of 0, 1000, and 2000 mg L-1 to the sub-plots. The findings demonstrated that plant height and leaf area considerably decreased with higher irrigation intervals while the highest concentration of ascorbic acid (2000 mg L-1) gave the maximum values for the two traits. Optical microscopy was used to examine anatomical changes under drought stress conditions in the stems and leaves of the soybean [Glycine max (L.) Merr. cv. Rami] plants, and numerical analysis assessed the importance of these alterations. Some differences in anatomical characteristics were found in the stressed soybean plants, including the size and average number of stomata and epidermal cells, as well as characteristics relating to the stem, leaf, and stomata indexes